MUKASYAFAH: PERSPEKTIF SUFISTIK - Cucu Setiawan (Syifa al-Qulub, 2016)
Mukasyafah is an individual state of people, to person is given by God (Allah Swt) and the function is abstract things and its only known by founder and God. The Spreading of massage it’s large founded, maybe it can cause fitna or negatives adjustment or can cause bad emotion like ujub (think perpect of self) and the effect can destroyed values of research.